HUBUNGAN BERAT BADAN LAHIR DENGAN RUPTUR PERINEUM DI BPS NY. ALIMAH KECAMATAN SOMAGEDE KABUPATEN BANYUMAS TAHUN 2009 - Pravitasari, Seva; ., Sumarni; Anasari, Tri (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2011)
Introduction: Postpartum haemorrhage has become the main cause of women mortality in Indonesia 40%. The phenomena in midwifery which lead to haemorrhage was the placenta, atone uteri,Â Â Â  and birth canal rupture. Birth canal rupture was the second reason of haemorrhage respectively after atonia uteriÂ Â  which occur almost in every first delivery process and so do the next delivery process.Â  One of rupture perineum reason was the overweight baby. Objectives: This research objective was to measure the correlation between low newborn baby weights toward rupture perineum occurrence at BPS. Ny. Alimah somagede sub-district of Banyumas Regency. Methods: This was analytic research with retrospective time approach.Â  The population was the entire normal give birth women and the amount was 80 persons, by total sampling technique and data was analyzed using chi-squre Results: most of baby which born through the normal delivery was 37 babies or 46,3%, while the overweight baby was 10 babies or 12,5%.Â  The delivery women was 50 persons or 62%, and the other 30 babies or 38% had perineum rupture.Â  The statistical analysis showed ï² = 0,000 means that the value of ï² < Î± 0,05 eans that there was a correlation between baby born weight toward rupture perineum occurrence. Suggestions: The health worker should increase the counselling regarding obstacle of delivery and perineum rupture. Â  Keyword : Newborn Baby Weight, Rupture Perineum Literature : 22 (1993 - 2009). 3 internets (2005 - 2009)